Enduring Roots : Encounters with Trees, History, and the American Landscape - Samuels, Gayle (Piscataway : Rutgers University Press, 1999)
Enduring Roots tells the stories of historic American trees, including the oak, the apple, the cherry, and the oldest of the world's trees, the bristlecone pine. These stories speak of our attachment to the land, of our universal and eternal need to leave a legacy, and demonstrate that the landscape is a gift, to be both received and, sometimes, tragically, to be destroyed.
Frontmatter -- Contents -- LIST OF ILLUSTRATIONS -- PREFACE -- ACKNOWLEDGMENTS -- CHAPTER ONE - TAKING ROOT: THE CHARTER OAK -- CHAPTER TWO - FAMILY TREES -- CHAPTER THREE - APPLES: CORE ISSUES -- CHAPTER FOUR - THREE CHERRIES -- CHAPTER FIVE - RETURNING NATIVES -- CHAPTER SIX - THE TREE THAT OWNED ITSELF -- CHAPTER SEVEN - METHUSELAH'S WALK -- NOTES -- BIBLIOGRAPHY -- INDEX -- About the author
Print version record.
Includes bibliographical references (pages 177-189) and index.
JSTOR
Keywords: Landscape assessment -- United States; Trees -- Environmental aspects -- United States; Trees -- Symbolic aspects -- United States; Trees -- United States -- Folklore; Paysages -- Évaluation -- États-Unis.; Arbres -- Aspect de l'environnement -- États-Unis.; Arbres -- Aspect symbolique -- États-Unis.; Arbres -- États-Unis -- Folklore; Landscape assessment; Trees; Trees -- Environmental aspects; Trees -- Symbolic aspects; United States; Folklore